1997
DOI: 10.3171/jns.1997.87.6.0851
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral posterior atlantoaxial transarticular screw fixation

Abstract: Bilateral posterior C 1-2 transfacet screw placement with associated posterior bone graft wiring is the accepted treatment for patients with atlantoaxial instability. This technique was modified to treat 19 patients with atlantoaxial instability and unilateral anomalies that prevented placement of a screw across the C1-2 facet. In these cases, a single contralateral transarticular screw was placed in conjunction with interspinous bone graft wiring to avoid neural or vertebral artery injury and to provide C1-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 26 publications
2
51
0
1
Order By: Relevance
“…Confirming previous studies [16,26], the present series showed that solid fusion can be achieved even if only one screw is placed ideally (e.g. following the inadvertent misplacement of the screw on the opposite side) and is combined with appropriate midline bone grafting.…”
Section: Discussionsupporting
confidence: 71%
“…Confirming previous studies [16,26], the present series showed that solid fusion can be achieved even if only one screw is placed ideally (e.g. following the inadvertent misplacement of the screw on the opposite side) and is combined with appropriate midline bone grafting.…”
Section: Discussionsupporting
confidence: 71%
“…It is the most effective biomechanical technique to attain C1-2 stability, and is superior to conventional wiring methods by virtue of more rigid fixation 18) . Solid atlantoaxial fusion has been reported in 80 to 100% of patients who were treated with this method 14,18) .…”
Section: Introductionmentioning
confidence: 99%
“…It is the most effective biomechanical technique to attain C1-2 stability, and is superior to conventional wiring methods by virtue of more rigid fixation 18) . Solid atlantoaxial fusion has been reported in 80 to 100% of patients who were treated with this method 14,18) . However, bilateral TAF across the C1-2 may be contraindicated or impossible in up to 20% of patients because of its structural disfigurements such as anomalous course of the vertebral artery (VA), comminuted fractures of C-1 or C-2, or other pathological processes 14) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some advantages connected with this technique have been described: first, it can be used even in the case of a so-called high-riding vertebral artery, which has been described to be as frequent as 10%-25%. 1,19,24 Second, repositioning of an anteriorly placed fragment is easy by soft tension applied to the atlas, especially if combined with pressure to the spinous process of C-2. Third, it was hypothesized that the segmental mobility within C1-2 could be preserved in case of implant removal.…”
Section: 20mentioning
confidence: 99%